Momentary affective response to bouts of moderate-to-vigorous physical activity predicts changes in physical activity and sedentary behavior during behavioral weight loss. (November 2021) - Smith, Kathryn E.; Mason, Tyler B.; Schumacher, Leah M.; Pellegrini, Christine A.; Goldschmidt, Andrea B.; Unick, Jessica L.
Abstract: Background: Affective responses are posited to be key predictors of the uptake and maintenance of health behaviors. However, few studies have examined how individuals' affective response to physical activity, as well as the degree to which their affect response changes, may predict changes in physical activity and sedentary time during behavioral weight loss treatment. Purpose: The current study examined how baseline momentary affective response (i.e., stress and anxiety) to moderate-to-vigorous physical activity (MVPA) and the degree of pre--post intervention change in this response predicted change in daily sedentary, light, and MVPA time during a three-month internet-based weight loss program. Methods: Women with overweight/obesity (final N  = 37) completed 14-day ecological momentary assessment (EMA) protocols with objective measurement of physical activity (i.e., bout-related MVPA time) before and after the intervention. Results: Women who had more reinforcing responses to MVPA (i.e., greater reductions in anxiety and stress response following MVPA bouts) at baseline had greater increases in overall MVPA at the end of the intervention. Those who had greater anxiety reductions after MVPA bouts at baseline also evidenced less sedentary time at the end of the intervention. Changes in affective responses across the intervention were not related to changes in physical activity levels. Conclusions: Findings suggest initial levels of affective reinforcement from MVPA bouts predict future change in MVPA and sedentary time during behavioral weight loss. Future work is needed to examine the utility of more precisely targeting affective responses to physical activity to optimize intervention approaches. Highlights: Affect response to physical activity (PA) may contribute to PA uptake and maintenance. Women with overweight/obesity were assessed at the beginning and end of a weight loss program. Ecological momentary assessment and accelerometers measured affect response to PA. More improvement in stress and anxiety after PA predicted better PA outcomes. Changes in affective response to PA were not related to PA outcomes.